DAKWAH KULTURAL MUHAMMADIYAH TERHADAP KAUM AWAM - Amrullah Husein (Ath Thariq Jurnal Dakwah dan Komunikasi, 2017)
Muhammadiyah as an Islamic movement based on the Qur'an and Sunnah with tajdid movement inherent in him always carrying the mission of amar ma'ruf nahi mungkar in all areas of life. In order to make Islam a rahmatan li al-'alamin then Muhammadiyah adopt various approaches and strategy of da'wah, among others through Cultural Da'wah. Cultural da'wah as an approach and strategy of da'wah in the context of actualization of Islamic teachings in the midst of the dynamics of culture and social change in a society run gradually in accordance with the conditions of local communities. The focus of cultural da'wah lies in awareness of faith so that people are willing to accept and fulfill all Islamic teachings covering aqidah, worship, morality, and muamalah by considering the stages of social change based on social, economic, cultural, and political plurality of a society so that finally the ideal stage Islamic society can be achieved as the main mission of the Islamic message. Muhammadiyah's concept of cultural propagation essentially relies on two aspects, aspects of dynamism and purification. First, the dynamics appreciate the potential and the tendency of human beings as cultural beings, to make efforts so that culture can bring to the progress and enlightenment of human life. Secondly, purification tries to avoid the preservation of culture that is evident in terms of Islamic teachings are shirk, superstition, bid'ah and khurafat.